A Practical and Cost-Effective Method for the Synthesis of Bicyclo[2.2.2]octane-1,4-dicarboxylic Acid - Le Marquer, Nicolas; Laurent, Mathieu Yves; Martel, Arnaud (Synthesis, 2015)
A short and efficient synthesis of bicyclo[2.2.2]octane-1,4-dicarboxylic acid involving the formation of a semicarbazone is developed, and a reproducible protocol for the reduction of this semicarbazone is described. The use of microwaves significantly shortens the duration of the sequence to the diacid compared to the previously described synthetic method. In addition, by shifting from the use of large amounts of Raney nickel to a solid-phase process, both the safety and cost are improved notably.
Keywords: bicyclo[2.2.2]octane-1,4-dicarboxylic acid; safe; semicarbazone; microwave irradiation; rigid backbone; solid-phase